Amine-Functionalized and Hydroxyl-Functionalized Magnesium Ferrite Nanoparticles for Congo Red Adsorption - Chattharika Aoopngan (2020)
Copyright © 2019 American Chemical Society. In this paper, the potential use of either amine-functionalized or hydroxyl-functionalized magnesium ferrite (MgFe2O4) nanoparticles (NPs) as Congo red nanoadsorbents is explored and compared. The amine-functionalized MgFe2O4 NPs (denoted as MgFe2O4-NH2 NPs) were synthesized by a one-pot coprecipitation method using ethanolamine as a surface modifier, while the hydroxyl-functionalized MgFe2O4 NPs (denoted as MgFe2O4-OH NPs) were prepared by a hydrothermal method. In general, both nanoadsorbents can be successfully produced without calcination and were found to possess superparamagnetic properties with high saturation magnetization (Ms). In particular, MgFe2O4-OH NPs exhibit a higher Ms value of ∼53 emu g-1, promoting the rapid separation ability of the NPs from the treated solution using an external permanent magnet. The Congo red removal performance of these nanoadsorbents was investigated as a function of the pH of the aqueous solution and contact time. The removal efficiency of Congo red by MgFe2O4-NH2 NPs was found to be ∼96% within 180 min at pH 6, while MgFe2O4-OH NPs provided a removal efficiency at ∼88% within 420 min at pH 8. In addition, the maximum adsorption capacities (qm) calculated using the Langmuir isotherm equation were found to be 71.4 and 67.6 mg g-1 for MgFe2O4-NH2 and MgFe2O4-OH NPs, respectively. The higher qm value of MgFe2O4-NH2 NPs could be attributed to stronger electrostatic interactions with the sulfonate groups of Congo red formed by larger numbers of protonated amine groups than protonated hydroxyl groups of the adsorbents under the performed conditions. Moreover, reusability experiments also revealed that MgFe2O4-NH2 NPs offered a higher removal efficiency than MgFe2O4-OH NPs for the same cycles tested. Therefore, this study demonstrates that MgFe2O4-NH2 NPs synthesized by a simple one-pot synthetic method are applicable as reusable magnetic nanoadsorbents for Congo red removal in current practice.